2023
DOI: 10.3390/nu15071701
|View full text |Cite
|
Sign up to set email alerts
|

HMOs Exert Marked Bifidogenic Effects on Children’s Gut Microbiota Ex Vivo, Due to Age-Related Bifidobacterium Species Composition

Abstract: Prebiotics are substrates that are selectively utilized by host microorganisms, thus conferring a health benefit. There is a growing awareness that interpersonal and age-dependent differences in gut microbiota composition impact prebiotic effects. Due to the interest in using human milk oligosaccharides (HMOs) beyond infancy, this study evaluated how HMOs [2’Fucosyllactose (2’FL), Lacto-N-neotetraose (LNnT), 3’Sialyllactose (3’SL), 6’Sialyllactose (6’SL)] and blends thereof affect the microbiota of 6-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…Supplementation of probiotics also resulted in the induction of beneficial metabolites, including L‐(−)‐3‐phenyllactic acid and trans‐cinnamic acid. These metabolites created an acidic environment, which serves as a favourable condition for beneficial microbes, especially Bifidobacteriaceae (Álvarez et al ., 2022; Bajic et al ., 2023). Moreover, both metabolites were found to be linked with a decrease in the possibility of accumulating fat.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of probiotics also resulted in the induction of beneficial metabolites, including L‐(−)‐3‐phenyllactic acid and trans‐cinnamic acid. These metabolites created an acidic environment, which serves as a favourable condition for beneficial microbes, especially Bifidobacteriaceae (Álvarez et al ., 2022; Bajic et al ., 2023). Moreover, both metabolites were found to be linked with a decrease in the possibility of accumulating fat.…”
Section: Discussionmentioning
confidence: 99%
“…In prior literature, 2’FL has been implicated in multiple functions including protection against infections, reduction of morbidity and use of antipyretics and antibiotics (26, 27); stimulation of brain development (28, 29); weight gain (19); and improvement of cognitive functions (30). 2’FL also promotes the selective growth of bifidobacteria and therefore probably influences the composition of gut microbiota (31) and microbiota-induced immune functions (32) in breastfeeding infants. 2’FL and 3’FL, which also increased during lactation in Ugandan mothers, have been implicated in the prevention of mortality in uninfected Zambian infants born to HIV-positive mothers (33).…”
Section: Discussionmentioning
confidence: 99%
“…2’FL and 3’FL, which also increased during lactation in Ugandan mothers, have been implicated in the prevention of mortality in uninfected Zambian infants born to HIV-positive mothers (33). The exact mechanisms by which HMOs reduce morbidity, prevent mortality and promote growth and development are unknown but could be associated with their reported anti-infective activities and effects on immunity (31,32, 34). The mechanisms underlying differences in HMO profiles during lactation remain speculative (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pig study showed that gut microbes could leverage metabolites produced by HMOs to induce structural changes in the brain and enhance cognitive function 120 . Additionally, human studies have demonstrated multiple roles for HMOs as modulators of the GM in children, influencers of colonization of Bifidobacteria in the infant gut, and facilitators of neonatal neurological development 121,122 …”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 99%